A Note on Innovation and Air Traffic Growth - Miller, Ronald E. (The Review of Economics and Statistics, 1966)
unique between levels of educational development and years of school completed. The relationship may differ from individual to individual, from country to country, and even from region to region within the United States. That is certainly a weakness of national calculations such as I made. It does not follow, however, that there are no averages of school years which are reasonably good predictors of levels of general educational development. The common practice of describing job qualifications in terms of education completed is, at least in part I believe, recognition of such an average relationship. Rather than describing my approach as circular as Ross does, I would call it partial. In calculating requirements I did not take into account the interdependence among types and levels of education and skills, either the complementarities or the substitution possibilities. I would agree with Ross that the requirements for, say, medical orderlies depend on the number of M.D.s and nurses available and the proportions in which it is decided, somehow, that they should work together. All I could claim to have done is to have estimated in some detail the situation for the United States at a certain time. I wouldn't recommend it for any other country nor would I even claim that it is an optimal situation for the United States. In this respect I might go even further than Ross and say, for example, that the . . skills, abilities, etc., required in a first-grade teacher . . . , are not similar everywhere, but depend on the educational objectives of the first grade and the educational system as a whole, the social structure, the resources available, and a lot of other things. All such factors should be taken into account when considering skill requirements for first-grade teachers or other personnel. I don't really believe in fixed proportions in the inputs of educated personnel into an economy and did not intend the percentages which I calculated to be taken as such. Partly for this reason I have refrained from making projections of future educational requirements for the United States with the percentages which I calculated. If this is done, the calculations should be made taking into account the changes which are desired and which are likely to occur. Economic criteria are not the only, nor perhaps even the most important criteria for education, but they were what I was concerned with.